2021
DOI: 10.1177/17470218211064583
|View full text |Cite
|
Sign up to set email alerts
|

Feelings first? Sex differences in affective and cognitive processes in emotion recognition

Abstract: The recognition of emotional expressions is important for social understanding and interaction, but findings on the relationship between emotion recognition, empathy and theory of mind, as well as sex differences in these relationships, have been inconsistent. This may reflect the relative involvement of affective and cognitive processes at different stages of emotion recognition and in different experimental paradigms. In the present study, images of faces morphed from neutral to full expression of five basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Females and males use different strategies during emotional processing tasks: while males recruit cognitive-related neural networks, females show neural activation in emotional-related areas (Derntl et al, 2010). A recent study showed that the sex differences in empathy were associated with sex differences in emotional processing: Females scored higher than male in affective empathy, but not cognitive empathy; these sex differences in affective empathy could explain shorter female reaction times in emotion recognition tasks (Bek et al, 2022). Thus, it is reasonable to speculate that the lack of association between RMET and emotional recognition in females could be due to the impact of higher affective empathy predisposition, which can compensate for lower levels of theory-of-mind capability in processing others' emotions.…”
Section: Effects Of Sex Cognitive Empathy and Alexithymia Traits On E...mentioning
confidence: 99%
“…Females and males use different strategies during emotional processing tasks: while males recruit cognitive-related neural networks, females show neural activation in emotional-related areas (Derntl et al, 2010). A recent study showed that the sex differences in empathy were associated with sex differences in emotional processing: Females scored higher than male in affective empathy, but not cognitive empathy; these sex differences in affective empathy could explain shorter female reaction times in emotion recognition tasks (Bek et al, 2022). Thus, it is reasonable to speculate that the lack of association between RMET and emotional recognition in females could be due to the impact of higher affective empathy predisposition, which can compensate for lower levels of theory-of-mind capability in processing others' emotions.…”
Section: Effects Of Sex Cognitive Empathy and Alexithymia Traits On E...mentioning
confidence: 99%
“…All covariates were mean centred. Moreover, since there is an implicit effect of face gender in emotion perception (e.g., Becker et al, 2007;Hess et al, 2009) and a women advantage in recognizing emotional faces (e.g., Bek et al, 2022), two exploratory repeatedmeasures ANOVA with Emotion (within-subjects factor) were conducted to test the effects of Avatar Sex (within-subjects factor) and Participant Sex (between-subjects factor).…”
Section: Preregistered Statistical Analysesmentioning
confidence: 99%
“…One possible key driver of the distinction between cognitive and affective ToM processes could be that emotion perception is more closely associated with affective than cognitive ToM. Emotion perception involves the ability to accurately read information about the emotional state of someone through verbal, bodily, and facial cues and is suggested to recruit partially distinct brain regions to cognitive and affective ToM (Bek et al, 2021 ; Mitchell & Phillips, 2015 ). Studies have shown that emotion perception performance is significantly correlated with affective ToM performance only (Bek et al, 2021 ; Henry et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotion perception involves the ability to accurately read information about the emotional state of someone through verbal, bodily, and facial cues and is suggested to recruit partially distinct brain regions to cognitive and affective ToM (Bek et al, 2021 ; Mitchell & Phillips, 2015 ). Studies have shown that emotion perception performance is significantly correlated with affective ToM performance only (Bek et al, 2021 ; Henry et al, 2006 ). However, it is currently unclear whether this correlation is due to shared emotion perception functions or due to similarities in task demands (i.e., identifying complex affective states versus basic emotions from face or eye region images; Bek et al, 2021 ; Henry et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation